Faktor-Faktor Yang Mempengaruhi Kepatuhan Membayar Pajak UMKM di Kabupaten Pekalongan - Lutfiyanah; Furqon, Imahda Khori (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This research has aimed to analyze the influence of good perception in the effectiveness of tax system, knowledge and comprehension about tax’ s obligation, and the trust of law system andadministration about loyalty in the UMKM tax payment in Pekalongan Regency. The population inthis research is UMKM tax obligatory in the category of an individual which has free traderegistered in tax office. Sampling methode in this research with accidental sampling there are 100respondent. The results of this research shows that the good perception of the effectiveness of taxsystem, knowledge and comprehension about tax’ s obligation partially influenced in the loyalty ofUMKM tax payment in Pekalongan Regency, while the level of trust in law system andadministration has no influence partially to the loyalty of UMKM tax payment in PekalonganRegency. The tax office to intensively socialize the government rule No. 46/2013 to the societyespecially the owner of UMKM to encourage the owner of UMKM to pay their tax